Metal-Free Arylalkylation of N-Aryl Acrylamides with Azobisalkylnitriles - Tian, Qingshan; He, Ping; Kuang, Chunxiang (Synlett, 2015)
A novel metal-free arylalkylation of N-aryl acrylamides with readily available azobisalkylnitriles leading to cyano-containing oxindoles has been developed. The use of readily available azobisalkylnitriles and DTBP as oxidant makes this protocol environmentally benign and practical.
Keywords: metal-free; aryalkylation; acrylamide; AIBN; oxindole